PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS INKUIRI TERBIMBING (GUIDED INQUIRY) PADA MATERI TRANSFORMASI GEOMETRI SMA KELAS XI - NOFIAH . (Jurnal Edukasi dan Penelitian Matematika, 2021)
This research is a development research which aims to produce a valid and practical Student Worksheet (LKPD) based on Guided Inquiry on Geometry Transformation Material. The development procedure used consists of the preliminary stage, making a prototype and an assessment. The results showed that the guided inquiry based LKPD on Geometry Transformation Material was valid and practical. The expert reviews stage obtained a valid LKPD result with a validity score of 74.14%. In the LKPD practicality category, seen from the six responses of students who had carried out the small group evaluation stage was 91, 32% with the very practical category. From the results obtained, the guided inquiry based LKPD can be declared valid and practical Keywords— development research, student worksheets, guided inquiry